Intensifikasi Kompetensi Guru Desa dalam Penguatan Kurikulum Praktikum Fisika Dasar di Tingkat Sekolah Menengah se-Kabupaten Kepulauan Meranti - Saktioto, Saktioto; Defrianto, Defrianto; Rini, Ari Sulistyo; Irawan, Dedi; Agrina, Agrina; Anita, Sofia; Soerbakti, Yan; Rabin, Mohammed Fisal (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Teacher competency standards are indicators that can be used as a measure of teacher characteristics that are considered professionally competent. Teachers have a very strategic role in efforts to realize national development goals, especially in the field of education. However, the goal of education is to experience a decline in competency standards at the end of each year for certain subjects, especially science / Basic Physics. Therefore, this service aims to motivate educators and students at the secondary school level to raise awareness of the education process through the practice of learning science / Basic Physics using adequate equipment and materials. The proposed form of activity is in the form of teaching and learning in secondary schools throughout the Meranti Islands Regency including SMA, MAN, and MTs, and SMP levels. In addition, this activity also provides guidance on experiments and demonstration tools for science / Basic Physics teachers regarding understanding concepts from simple to complex natural phenomena through simple demonstration media for practical tools. That way, teachers are expected to be motivated and enthusiastic in the learning process with a good and comprehensive understanding of the material. So that it can increase teacher competency standards intensively to be more qualified and professional.